Nothing short of wondrous [large type] - Scott, Regina, 1959- (Scott, Regina, 1959- American wonders collection, 2022)
"It is 1886, and the government has given the US Cavalry control of Yellowstone. For widowed hotelier Kate Tremaine, the change is a welcome one. She knows every inch of her wilderness home like the back of her hand and wants to see it protected from poachers and vandals. Refused a guide by Congress, Lieutenant William Prescott must enlist Kate's aid to help him navigate the sprawling park and track down the troublemakers. But a secret from his past makes him wary of the tender feelings the capable and comely widow raises in him. As they work together to protect the park and stand firm through injustice and tragedy, they may just find that two wounded hearts can share one powerful love when God is in control"-- Provided by publisher.